1992
DOI: 10.1111/j.1528-1157.1992.tb02195.x
|View full text |Cite
|
Sign up to set email alerts
|

Ictal and Interictal Activity in Partial Epilepsy Recorded with Multichannel Magnetoelectroencephalography: Correlation of Electroencephalography/Electrocorticography, Magnetic Resonance Imaging, Single Photon Emission Computed Tomography, and Positron Emission Tomography Findings

Abstract: Ictal and interictal epileptic activity was recorded for the first time by multichannel magnetoencephalography (MEG) in three patients with partial epilepsy. Pre- and intra-operative localization of the epileptogenic region was compared. The interictal epileptic activity was localized at the same region of the temporal or frontal lobe as the ictal activity. Main zones of ictal activity were shown to evolve from the tissue at the centers of interictal activity. Pre- and intra-operative electrocorticography (ECo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
60
0
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(68 citation statements)
references
References 14 publications
4
60
0
4
Order By: Relevance
“…Spike localization by magnetoencephalography (MEG) has been compared with localization by intracranial EEG (2,(9)(10)(11)(12)(13)(14), positron emission tomography (PET) (15) and single-photon emission computed tomography (SPECT) (9). Previous studies suggested that the localization accuracy of MEG was higher than that of conventional scalp EEG (10,14) because of the absence of disturbance by the inhomogeneous conductivity of cranial tissues.…”
mentioning
confidence: 99%
“…Spike localization by magnetoencephalography (MEG) has been compared with localization by intracranial EEG (2,(9)(10)(11)(12)(13)(14), positron emission tomography (PET) (15) and single-photon emission computed tomography (SPECT) (9). Previous studies suggested that the localization accuracy of MEG was higher than that of conventional scalp EEG (10,14) because of the absence of disturbance by the inhomogeneous conductivity of cranial tissues.…”
mentioning
confidence: 99%
“…Magnetoencephalography (MEG) is a noninvasive neurophysiologic technique to detect the magnetic fields generated by electric currents in the brain, and has been frequently used to localize the epileptic discharges in patients with focal epilepsy (Stefan et al 1992;Nakasato et al 1994;Knowlton et al 1997;Jin et al 2007), but not in patients with insular epilepsy.…”
mentioning
confidence: 99%
“…Several noninvasive and interictal diagnostic approaches have been implemented in the presurgical evaluation programs in intractable epilepsy syndromes of uniregional origin, all of them with the intention (a) to add to the complementary information about a regional functional deficit or morphologic lesion corresponding to the hypothesized primary epileptogenic zone, and (b) to reduce the number of invasive EEG recordings (26)(27)(28)(29). For this purpose, the most promising aspect of EEG dipole-source analysis is the theoretic possibility to ameliorate the poor spatial resolution of spikes recorded from the scalp in depth.…”
Section: Discussionmentioning
confidence: 99%